2014
DOI: 10.2109/jcersj2.122.530
|View full text |Cite
|
Sign up to set email alerts
|

Bulk, interface and surface properties of zinc oxide

Abstract: Zinc oxide (ZnO) is a highly developed oxide semiconductor that has been widely employed in industry as varistor ceramics, transparent conductor films, surface acoustic wave resonators, and so on. However, many questions about its fundamental properties remain unanswered. For instance, density functional theory simulations are currently contradicting the common conception established by many experimental scientists that non-stoichiometry is the primary factor inducing the native conductivity of ZnO. Thus, it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Surface terminations can be defined as either polar Zn-terminated-surface (Zn-surface) or oxygen-terminated-surface (O-surface) and can have an effect on film growth and final film properties. Previous studies have been devoted to understanding the relationship between polarity and the presence of impurities, defect incorporation, and orientation of the crystalline facet. For example, the impurity incorporation behavior in homoepitaxial ZnO films depends on the orientation of growth facet. , In addition, it has been reported that impurities, which can be regarded as potential donors, can be easily incorporated into the ZnO lattice on the O-surface . However, impurities, which are the cause of acceptor states in ZnO, are incorporated on the Zn-surface .…”
Section: Introductionmentioning
confidence: 99%
“…Surface terminations can be defined as either polar Zn-terminated-surface (Zn-surface) or oxygen-terminated-surface (O-surface) and can have an effect on film growth and final film properties. Previous studies have been devoted to understanding the relationship between polarity and the presence of impurities, defect incorporation, and orientation of the crystalline facet. For example, the impurity incorporation behavior in homoepitaxial ZnO films depends on the orientation of growth facet. , In addition, it has been reported that impurities, which can be regarded as potential donors, can be easily incorporated into the ZnO lattice on the O-surface . However, impurities, which are the cause of acceptor states in ZnO, are incorporated on the Zn-surface .…”
Section: Introductionmentioning
confidence: 99%
“…There is now a considerable body of CLS research on ZnO, motivated by its potential for optoelectronic and microelectronic applications 69 and based on a number of factors: its 60 meV exciton binding energy for efficient light emitters, high mobility transport, 70 ease of large area growth, 71 wet chemical processing, resistance to space radiation, and environmental compatibility. For a general review of ZnO materials and devices, see Özgür et al 72 Extended to the nanoscale, CLS can describe how ZnO properties vary within interfaces, micro-and nanostructures together with how they can depend on growth and processing.…”
Section: Introductionmentioning
confidence: 99%